Syntaxonomy of cl. Phragmito-magnocaricetea (ord. Phragmitetalia, Bolboschoenetalia maritima, Nasturtio-Glycerietalia) in the Kremenchug storage pool (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
There are 13 associations belonged to orders Phragmitetalia, Bolboschoenetalia maritima and Nasturtio-Glycerietalia in the Kremenchug reservoir. A classification scheme developed using Braun-Blanquet approach with coenotic analysis and distribution patterns of communities studied.
Keywords: Kremenchug reservoir, syntaxonomy, air-water vegetation.